(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Forests provide a variety of ecosystem services essential for human well-being, with recreation and ecotourism increasingly recognised as valuable non-market benefits. This study assesses the economic value of forest ecosystem services and visitors’ perceptions of recreational and conservation roles within two selected Eco Parks in Perak, Malaysia, namely Taman Eko-Rimba (TER) Lata Iskandar and TER Pasir Panjang. Using the Contingent Valuation Method (CVM), primary data were collected through structured surveys of 501 visitors (with a minimum of 250 respondents per site) to estimate their willingness to pay (WTP) for continued recreational access and enhanced conservation initiatives. The findings reveal that recreational and ecotourism services contribute significantly to the local economy through notable non-market values and individual WTP estimates. The OLS and Logistic regression models show mean WTP values of RM5.85 (OLS) and RM8.80 (Logit) for TER Lata Iskandar, and RM8.10 (OLS) and RM10.50 (Logit) for TER Pasir Panjang. Key significant determinants of WTP include income, education, visit frequency, visit duration, and repeat visitation, underscoring the influence of socio-economic capacity and behavioural factors on conservation support. Most visitors expressed strong support for conservation initiatives and recognised the importance of Eco Parks in providing environmental education, biodiversity protection, and community benefits. Positive visitor perceptions further reinforce the role of Eco Parks as essential assets for sustainable tourism and rural economic development. This study highlights the importance of integrating both economic valuation and public perception into forest management strategies to enhance conservation financing, improve visitor experiences, and support community livelihoods